EFEKTIVITAS PEMBUATAN KTP DENGAN PROGRAM SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) - Suciptawati, Ni Luh Putu (PIRAMIDA; Vol. 7, No.1 Juli 2011)
KTP is formal ID card Indonesian people which provided by government official. Thisresearch aimed to know efectivity KTP production by SIAK program. Data that used in thisresearch were quantity KTP request 6 years before and 6 years after SIAK program used.Data were analysed using t-student test. The result showed KTP production by SIAK programmost effective.
Keywords: KTP, SIAK program